REKONSTRUKSI PENGATURAN PEMBINAAN LEMBAGA KEOLAHRAGAAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 19/PUU-XII/2014 - Hermawan Dwi Putra; Tunggul Anshari; Muhammad Lutfi (Faculty of Law, University of Muhammadiyah Malang, 2019)
The study, titled “Reconstruction Of The Sport Institute Coaching Arragements In Legislation” aims to analyze the No. 3 Year 2005 about the National Immune System in the second generation of adults, the political system in Indonesia and the form of breaking up in the Constitution. The method used in this study is normative legal research, the approach taken Law approach, historical approach and comparative approach, there are three sources of legal material, namely the source of primary, secondary and tertiary legal materials. The legal material collection technique analyzes the Minutes of the Indonesian National System, a study of students by collecting and analyzing the population, as well as researchers from the internet. The analysis of the law in the study with descriptive descriptive techniques of the. The results showed that the problem can be concluded as the cause of the obscurity of the norms of the National Sports Committee in 36 articles (1) and (3), based on the SKN Draft Bill, the KONI is written National Sports with the aim to protect the citizenship of KONI. KOI only has to go to the internet and it will take an internal competition. The overlapping of authority in the development of sports due to the absence of legal certainty. Giving the concept of setting up KONI and KOI after being in the mid-1980s, KONI and KOI will eventually be led by a third, Reconstruction in the SKN Law makes it appear that it has a disadvantage so it does not cause conflict.